Students’ Learning Motivation through Ice Breaking in Indonesian Language Learning: Motivasi Belajar Peserta Didik melalui Ice Breaking dalam Pembelajaran Bahasa Indonesia - Ali Raksan Yani; Tri Wera Agrita; Reni Guswita (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Motivation is a crucial factor in determining students’ success in language learning, particularly at the elementary level. Specific Background: Observations at MIS Assu’udiyah revealed that the integration of ice breaking activities in Indonesian language learning fostered enthusiasm and classroom engagement. Knowledge Gap: Although prior studies addressed motivation, limited research has examined how structured ice breaking activities sustain students’ motivation in elementary Indonesian language classes. Aim: This study explores the forms of motivation demonstrated by students and the strategies they adopt during lessons supported by ice breaking. Results: Using qualitative case study methods with interviews and thematic analysis, findings indicate that both internal factors (interest, persistence, curiosity) and external factors (teacher encouragement, positive class atmosphere, peer interaction) shape students’ motivation. Ice breaking helped reduce tension, increased participation, and promoted joyful learning experiences. Novelty: Unlike general motivational studies, this research emphasizes the role of interactive and playful activities as a consistent pedagogical strategy in early language acquisition. Implications: Integrating ice breaking into routine lesson planning may serve as a practical approach for teachers to sustain motivation, emotional readiness, and active participation in elementary classrooms. Highlight Students showed high enthusiasm and focus during ice breaking activities. Internal and external factors jointly shaped learning motivation. Ice breaking created a positive and engaging classroom atmosphere. Keywords Learning Motivation, Ice Breaking, Indonesian Language Learning, Elementary Students, Classroom Engagement